The Effect of Utilizing Macromedia Flash as a Teaching Media for Delivering Integer on The Learning Outcomes of The Seventh Graders of Mts Miftahul Ulum Pelangwot - Adawiyah, Robiah; Stani, Dwinta; Setyabekti, Rengga Adi; Iffah, Jauhara Dian Nurul; Masruroh, Faridatul (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This study aimed to see the significant effect of utilizing Macromedia Flash as a teaching media for delivering integer on the learning output of the seventh graders of MTs Miftahu Ulum Pelangwot. It was an experimental research with a control design of one group pre-test post-test design. Hence, it used pre-test and post-test questions as the research instrument. Some tests including validity test, reliability test, and hypothesis test using Paired Sample T-test were all applied for data analysis. The research instrument was validated by an expert validator who confirmed that it was proper to use. The significant result of normality test was 0,2, which was more than 0,05, indicating that the data was normally distributed. The result of Paired Sample Test was tcount > ttable referring to 5,950>2,160. Therefore, it concluded that the significant effect of utilizing Macromedia Flash as a teaching media for delivering integer on the learning outcomes of the seventh graders of MTs Miftahul Ulum Pelangwot obviously existed.